Tumour necrosis factor‐α contributes to improved cardiac ischaemic tolerance in rats adapted to chronic continuous hypoxia. (28th March 2015) - Chytilová, A.; Borchert, G. H.; Mandíková‐Alánová, P.; Hlaváčková, M.; Kopkan, L.; Khan, Md. A. Hye; Imig, J. D.; Kolář, F.; Neckář, J.
Abstract Aim It has been demonstrated that tumour necrosis factor‐alpha (TNF‐α) via its receptor 2 (TNFR2) plays a role in the cardioprotective effects of preconditioning. It is also well known that chronic hypoxia is associated with activation of inflammatory response. With this background, we hypothesized that TNF‐α signalling may contribute to the improved ischaemic tolerance of chronically hypoxic hearts. Methods Adult male Wistar rats were kept either at room air (normoxic controls) or at continuous normobaric hypoxia (CNH; inspired O2 fraction 0.1) for 3 weeks; subgroups of animals were treated with infliximab (monoclonal antibody against TNF‐α; 5 mg kg−1, i.p., once a week). Myocardial levels of oxidative stress markers and the expression of selected signalling molecules were analysed. Infarct size (tetrazolium staining) was assessed in open‐chest rats subjected to acute coronary artery occlusion/reperfusion. Results CNH increased myocardial TNF‐α level and expression of TNFR2; this response was abolished by infliximab treatment. CNH reduced myocardial infarct size from 50.8 ± 4.3% of the area at risk in normoxic animals to 35.5 ± 2.4%. Infliximab abolished the protective effect of CNH (44.9 ± 2.0%). CNH increased the levels of oxidative stress markers (3‐nitrotyrosine and malondialdehyde), the expression of nuclear factor κB and manganese superoxide dismutase, while these effects were absent in infliximab‐treated animals. CNH‐elevated levels of inducible nitric oxide synthase and cyclooxygenase 2 were not affected by infliximab. Conclusion TNF‐α plays a role in the induction of ischaemia‐resistant cardiac phenotype of CNH rats, possibly via the activation of protective redox signalling.